Effects of pre‐analytical heat treatment in factor VIII (FVIII) inhibitor assays on FVIII antibody levels. Issue 3 (20th February 2018) - Boylan, B.; Miller, C. H.
Abstract : Introduction: The use of pre‐analytical heat treatment (PHT) with the Nijmegen‐Bethesda assay (NBA) for inhibitors to factor VIII (FVIII) can remove/destroy infused or endogenous FVIII from patient plasma samples, allowing testing of recently infused patients with haemophilia. Two PHT methods have been described as follows: heating to 56°C for 30 minutes and heating to 58°C for 90 minutes. Data examining the effects of PHT on anti‐FVIII IgG4, the antibodies known to correlate most closely with the presence of FVIII inhibitors, are limited. Aim: To assess the effect of PHT on the levels of detectable anti‐FVIII IgG4 . Methods: Nijmegen‐Bethesda assay‐positive specimens were incubated at 56, 58 or 60°C for 90 minutes, and anti‐FVIII IgG4 was measured by fluorescence immunoassay (FLI) at 30‐minute intervals. The effects of PHT on the ability of recombinant FVIII (rFVIII) to inhibit detection of patient antibodies by FLI was also examined to assess the stability of rFVIII under the various PHT conditions tested. Results: Levels of anti‐FVIII IgG4 showed little change following incubations at 56°C (mean 101% of original value at 30 minutes and 100% at 60 minutes) but decreased upon exposure to 58°C (mean 85% at 30 minutes and 66% at 60 minutes). In addition, heating to 56°C effectively decreased the ability of rFVIII to block antibody binding compared to unheated rFVIII. Conclusion: The optimal temperature for PHT in the FVIII NBA is 56°C. Higher temperatures may lead to loss of inhibitory antibodies.